1985
DOI: 10.1088/0031-9155/30/7/001
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of mammalian brain tissue between 1 and 18 GHz

Abstract: A newly developed frequency domain technique was used to measure the dielectric properties of white matter, grey matter and macerated rabbit brain at 20 and 37 degrees C. An analysis of the data showed that between 1 and 4 GHz there were substantial contributions from processes other than the gamma dispersion. However, above 7.5 GHz it appeared that mainly free water was relaxing although evidence of a small spread of relaxation times was found for the bulk water in the white matter. Mouse and rat brain were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The IT’IS data on white matter, grey matter and cerebellum permittivity originate from Gabriel [ 20 ]. The values for brain tissues in the frequency range from 500 MHz to 18 GHz in Gabriel [ 20 ] were compiled from the literature already published at that time (i.e., before 1996): rabbit specimen at 37 °C [ 31 ] (white and grey matter), mouse specimen at 37 °C [ 32 ] (grey matter), rat specimen in vivo at 32 °C [ 33 ] (grey matter), feline specimen in vivo at 36 °C [ 33 ] (grey matter), canine specimen in situ at 36 °C [ 34 ] (white and grey matter), canine specimen at 20 °C [ 35 ] (white and grey matter), feline specimen in vivo at 33 °C [ 36 ] (white and grey matter), canine specimen at 37 °C [ 37 ] (white and grey matter), as well as from her own measurement results.…”
Section: Discussionmentioning
confidence: 99%
“…The IT’IS data on white matter, grey matter and cerebellum permittivity originate from Gabriel [ 20 ]. The values for brain tissues in the frequency range from 500 MHz to 18 GHz in Gabriel [ 20 ] were compiled from the literature already published at that time (i.e., before 1996): rabbit specimen at 37 °C [ 31 ] (white and grey matter), mouse specimen at 37 °C [ 32 ] (grey matter), rat specimen in vivo at 32 °C [ 33 ] (grey matter), feline specimen in vivo at 36 °C [ 33 ] (grey matter), canine specimen in situ at 36 °C [ 34 ] (white and grey matter), canine specimen at 20 °C [ 35 ] (white and grey matter), feline specimen in vivo at 33 °C [ 36 ] (white and grey matter), canine specimen at 37 °C [ 37 ] (white and grey matter), as well as from her own measurement results.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of prior studies in the microwave and millimeter-wave bands on the dielectric properties of brain tissue [53][54][55][56], tissue and head modeling [57][58][59][60] and RF energy exposure modeling [61][62][63][64][65][66][67][68]. Here, we study simultaneously the effects of beam penetration, absorption and thermal diffusion in brain tissue through realtime temperature measurements during the irradiation.…”
Section: Introduction To This Studymentioning
confidence: 99%
“…A survey of the literature showed that most of the research on dielectric properties on biological samples was done on nonliving tissue. Regarding brain tissue, which is of special interest for the exposure of the human head from modern handheld communication devices, most of this work was done in vitro on various animal tissues Thurai et al, 1984;Steel and Sheppard, 1985;Surowiec et al, 1986a;Xu et al, 1987;Gabriel et al, 1996]. In vivo measurements of the dielectric properties of brain tissue were reported by Stuchly et al [1981], Kraszewski et al [1982], and Burdette et al [1986] using cats, dogs, and rats as test animals.…”
Section: Introductionmentioning
confidence: 99%